Revisiting (and connecting) Marglin-Bhaduri and Minsky: an SFC look at financialization and profit-led growth - Cláudio H. dos Santos; Antonio Carlos Macedo e Silva (Levy Economics Institute of Bard College, 2009)
Many heterodox strands of thought share both a concern with the study of different phases or growth regimes in the history of capitalism and the use of formal short-run models as an analytical tool. This text suggests that: (1) this strategy is potentially misleading; (2) that the stock-flow consistent (SFC) approach, while providing a general framework that may facilitate the dialogue among those currents, is particularly well suited to all those who think that macroeconomic models may illuminate historical quests; and (3) this approach's main intuitions may be conveyed through the benchmark Post Keynesian SFC model presented by Dos Santos and Zezza (2008), dispensing with the complex computer simulations that are normally employed by SFC authors.
Keywords: B50; E12; 330; Stock-flow consistency; long-run analyses; post Keynesian macroeconomics; neo-Kaleckian macroeconomics; régulation school; financialization